Catalytic asymmetric synthesis of α-methyl-p-boronophenylalanine. Issue 10 (1st June 2018) - Harada, Shingo; Kajihara, Ryota; Muramoto, Risa; Jutabha, Promsuk; Anzai, Naohiko; Nemoto, Tetsuhiro
Graphical abstract: Highlights: We designed a novel candidate molecule for BNCT. ( S )-2-Amino-3-(4-boronophenyl)-2-methylpropanoic acid was synthesized. Phase-transfer catalyzed asymmetric alkylation was utilized as a key step. A Miyaura borylation reaction enabled the introduction of a boron functionality. Abstract: p -Boronophenylalanine (l -BPA) is applied in clinical settings as a boron carrier for boron neutron capture therapy (BNCT) to cure malignant melanomas. Structural modification or derivatization of l -BPA, however, to improve its uptake efficiency into tumor cells has scarcely been investigated. We successfully synthesized ( S )-2-amino-3-(4-boronophenyl)-2-methylpropanoic acid in enantioenriched form as a novel candidate molecule for BNCT. Key steps to enhance the efficiency of this synthesis were enantioselective alkylation of N -protected alanine tert -butyl ester with a Maruoka catalyst and Miyaura borylation reaction to install the boron functionality.